The construction and dynamics of cultural icons - Boven, Erica van, 1952-; Winkler, Marieke (Heritage and memory studies, 2021)
Departing from the present need for cultural models within the public debate, this volume offers a new contribution to the study of cultural icons. From the traditional religious icon to the modern mass media icon, from the recognizable visual icon to the complex entanglement of image and collective narratives: 'The Construction and Dynamics of Cultural Icons' offers an overview of existing theories, compares different definitions and proposes a comprehensive view on the icon and the iconic. Focusing in particular on the making of iconic representations and their changing social-cultural meanings through time, scholars from cultural memory studies, art history and literary studies present concrete operationalizations of the ways different types of cultural icons can be studied.